Assessment of Spirometry in Patients with Chronic Obstructive Pulmonary Disease and Its Correlation with High-Resolution Computerized Tomographic Scan Findings: Life Sciences-Corneal Thickness in Diabetic Retinopathy - Ganapathy, S.Thiyagesa Deva; K, Udhayakumar; Pajanivel, R (International Journal of Life Science and Pharma Research, 2022)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic inflammatory lung disease characterized by persistent airway inflammation. Spirometry is considered a gold standard for diagnosing COPD severity, high Resolution CT is needed for the analysis of various phenotypes of COPD and to quantify emphysema. Therefore, we conducted a study for assessment of the clinical severity of COPD using spirometry and correlating it with the High-Resolution CT finding. The present study subjects were new and previously diagnosed COPD patients who were fulfilling the inclusion criteria were enrolled in the study. The total study population is 45 patients. All the Patients who are enrolled in the study were subjected to pulmonary function test assessment and they are subjected to High Resolution Computed Tomography and the severity is correlated. Among 45 patients enrolled in the study, the majority of the patients were in the age group of more than 61 years (71.1%).13.3% of patients had mild COPD, 51.1 % moderate COPD, 26.7% severe and 8.8% very severe COPD patients with mean post-bronchodilator FEV1 (57.17) based on GOLD guidelines. In our study 44.4 % are smokers, 20 %are Ex-smokers and 35.6% are non-smokers. Out of the non-smokers, 10 were female and 6 were male patients (37.5%) and Smoking status is statistically significant in our study with a P value of 0.023. On correlating the High Resolution CT finding with the Spirometry, 35 patients had bronchial wall thickening, on comparing it with the COPD GOLD staging mild (33%), moderate (69%), severe (92%, very severe (100%). The p-value is 0.025. Emphysema was seen in 83%(n=5/6) of mild, 91% of moderate 75% of severe, and 100% of very severe patients and it correlated well with Spirometry and the p-value is 0.005, Mean lung density decreased with a decrease in Post FEV1%. The severity of emphysema and Bronchial wall thickening correlated well with the High-Resolution CT finding and they showed a positive correlation with Post FEV1.